2019
DOI: 10.3340/jkns.2018.0064
|View full text |Cite
|
Sign up to set email alerts
|

Selective Temporary Stent-Assisted Coil Embolization for Intracranial Wide-Necked Small Aneurysms Using Solitaire AB Retrievable Stent

Abstract: ObjectiveStent-assisted coil embolization of intracranial wide-necked aneurysm requires long-term postoperative antiplatelet therapy to prevent in-stent thrombosis. This study aimed to demonstrate results of temporary stent placement for coiling wide necked small intracranial aneurysms, which eliminated need for antiplatelet agents, and to discuss its feasibility and safety. MethodsData of 156 patients who underwent stent-assisted coil embolization between 2011 and 2014 were retrospectively analyzed. Thirteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Temporary stenting has been suggested as an alternative to the well-established remodeling techniques of balloonassisted coil embolization and stent-assisted coil embolization. To the best of our knowledge, however, since the first report on this technique in 2013, only 6 case reports or small case series have been published with a total number of reported cases of 65 [4,[6][7][8][9][10]. This already included 33 cases from our own group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporary stenting has been suggested as an alternative to the well-established remodeling techniques of balloonassisted coil embolization and stent-assisted coil embolization. To the best of our knowledge, however, since the first report on this technique in 2013, only 6 case reports or small case series have been published with a total number of reported cases of 65 [4,[6][7][8][9][10]. This already included 33 cases from our own group.…”
Section: Discussionmentioning
confidence: 99%
“…The CATS is an established standard technique in our institution for the treatment of wide-neck aneurysms. To date, only case reports and small case series on this technique have been published [4,[6][7][8][9][10]. To assess safety and effectiveness of CATS, we performed a retrospective intention-to-treat analysis of all consecutive patients, who were intended to be treated with CATS over a period of 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…However, when performing this technique, it is necessary to exclude the possibility of complete coagulation of hematoma blood by IVUS examination, and to avoid the microcatheter becoming stuck between the vessel wall and stent struts by pulling back the microcatheter slightly proximally to check the degree of resistance while slowly inflating the stent balloon. This procedure is acceptable because stent-traps for microcatheters are commonly used during coiling in neurointerventional radiology ( 3 ). If the aspiration method does not work after sealing the entry site by stenting, cutting balloon dilation at a distal site should be considered to create a re-entry at this point.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of dual antiplatelet maintenance therapy is the most important advantage of this technique. 18,19 Sirlov et al 20 treated acutely ruptured basilar artery bifurcation aneurysms with simultaneous Cascade and Comaneci temporaryassisted coiling. Their findings suggested that this method may be an alternative treatment to YSAC, especially in patients with acute ruptured aneurysms.…”
Section: Discussionmentioning
confidence: 99%